Transvenous lead revision for cardiac perforation: a single centre experience. (24th May 2021) - Elbatran, A; Akhtar, Z; Bajpai, A; Leung, L WM; Li, A; Pearse, S; Zuberi, Z; Kaba, R; Saba, M; Norman, M; Grimster, A; Gallagher, MM; et al.
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Cardiac perforation is an uncommon but life-threatening complication of cardiac implantable electronic device (CIED) implantation. Management strategy commonly relies on diagnostic Computed Tomography (CT) imaging and cardiac surgery. Emerging evidence has indicated a diversion from this approach. Transvenous culprit lead revision has been shown to be safe and efficacious in limited series. We sought to evaluate the outcomes of transvenous lead revision in patients with cardiac perforation. Method: Data was collected retrospectively of patients admitted to a single tertiary centre with CIED-related cardiac perforation between December 2013 – October 2019. Transvenous lead revision was performed as standard with cardiac surgery on standby. Patient demographics, use of CT imaging, method of removal and 30-day outcomes were recorded. Results: Of the 46 recorded CIED-related cardiac perforations, the majority occurred in female patients (63%) and hypertensives (61%), whilst a proportion had cancer (20%) and ischaemic heart disease (30%). The culprit in most cases was a standard pacing lead (92%) of an active fixation (98%) in the right ventricle (80%) positioned at the ventricular apex (65%). The median time to presentation from implant was 14 days [IQR 4-50 days] with chest pain (44%); abnormal pacing indices was highly prevalent (95%) whilst a pericardial effusion was noted in the majority of cases (57%). CT scanning was performed in 19 cases (41%) for various indications but deemed essential in only 4, all of which had non-diagnostic pacing indices and imaging. Chest X-ray (CXR) found clear perforation, lead displacement or pleural effusion in 74% of cases, whilst an echocardiogram found these in 64% of cases. The culprit lead was replaced in the majority of cases (87%) under local anaesthesia (76%) with surgical backup. The median hospital stay was 7 days [IQR 3-10 days] with zero procedural and 30-day mortality. Conclusion: Transvenous lead revision for CIED-related cardiac perforation is safe and efficacious. CT modality for diagnostic purposes is useful in providing incremental value in a minority of cases; patients with non-diagnostic pacing parameters and non-CT imaging benefit most from this.